2012
DOI: 10.1016/j.biopsych.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Concussive Brain Injury Enhances Fear Learning and Excitatory Processes in the Amygdala

Abstract: Background Mild traumatic brain injury (mTBI; cerebral concussion) results in cognitive and emotional dysfunction. These injuries are a significant risk factor for the development of anxiety disorders including post-traumatic stress disorder (PTSD). However, because physically traumatic events typically occur in a highly emotional context, it is unknown whether TBI itself is a cause of augmented fear and anxiety. Methods Rats were trained with one of five fear conditioning procedures (N = 105) two days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 55 publications
7
111
3
Order By: Relevance
“…Several studies have reported increased anxiety-like behavior in rodent TBI models, [29][30][31][32] including increased conditioned 33 and unconditioned 34 fear responses to both learned and novel stimuli. TBI in rodents also increases levels of activated glial cells and proinflammatory cytokines, [34][35][36][37][38] and administration of these cytokines increases anxiety-like behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported increased anxiety-like behavior in rodent TBI models, [29][30][31][32] including increased conditioned 33 and unconditioned 34 fear responses to both learned and novel stimuli. TBI in rodents also increases levels of activated glial cells and proinflammatory cytokines, [34][35][36][37][38] and administration of these cytokines increases anxiety-like behaviors.…”
mentioning
confidence: 99%
“…97,99,100 Other neuroimaging reports of patients with non-trauma-related OCD and phobia, as well as those with PTSD, have revealed that aversive anticipation (a hallmark of anxiety) involves increased activation of both the amygdala and insula. 92 Evidence for the specific involvement of these brain areas in human post-traumatic anxiety is complemented by animal models, including findings of increased PTSD-related traits and increased Stathmin 1 (a protein known to increase fear responses) expression in the amygdala after blast injury, 101 increased fear conditioning and up-regulation of excitatory N-methyl-D-aspartate receptors (crucial receptors for normal fear learning and memory) in the amygdala after concussive injury, 33 and our current results showing increased anxiety-like behavior and reactive gliosis in insula and amygdala at long-term time points after LFPI. However, though these results support findings from our previous study 34 indicating increased gliosis in these areas, the insula and amygdala are not the only regions involved in anxiety and do not exclude the possibility that other regions may be contributing to the results reported here.…”
mentioning
confidence: 99%
“…The N-methyl-D-aspartate (NMDA) glutamate receptors in the amygdala appear to regulate fear and anxiety. In a rat model of mild TBI, the levels of NMDA receptors in the amygdala increased while the levels of gamma-aminobutyric acid (GABA) decreased (Reger et al, 2012). Excitatory events created by an elevation of NMDA receptors levels and a decrease in GABA activity may increase the risk for developing fear and anxiety.…”
Section: Glutamate Release In Mild Tbimentioning
confidence: 99%
“…Glial activation is normally neuroprotective (26,32); however, the chronic inflammatory responses and exaggerated proinflammatory cytokine levels observed following injury initiate neurotoxic processes resulting in secondary tissue damage (20,(33)(34)(35), neuronal death (29,(36)(37)(38), secondary injury cascades (39)(40)(41)(42)(43) and neuronal hyperexcitability (28, 34, 38, 44). There is substantial support for chronic inflammation following TBI.…”
Section: Post-traumatic Anxiety Is a Leading And Devastating Consequementioning
confidence: 99%
“…The ongoing inflammatory response to tissue injury may contribute to damage and dysfunction in brain regions associated with anxiety, as TBI has been found to induce both acute and chronic neurodegeneration that could be caused by delayed cellular death pathways initiated by complex signaling cascades in activated glial cells (49,50). Several new lines of evidence support this hypothesis: (a) innate immune responses triggered by TBI (20,34,35), (b) resultant prolonged post-traumatic release of proinflammatory cytokines by activated glial cells (29,33,51,52), (c) chronic peripheral elevations of proinflammatory cytokines in patients with PTSD and panic disorder (19,21,23,24), (d) increased levels of activated microglia and astrocytes, IL-1β, TNF-α and IL-6 following controlled cortical impact and weight drop injury in rats (53)(54)(55)(56), (e) increased anxiety-like behavior (57)(58)(59)(60), and (f) elevated plasma corticosterone concentrations (61) when these cytokines are administered centrally or systemically in rats. Overall, these findings provide evidence for a potential role of the neuroimmune system in the pathophysiology of posttraumatic anxiety.…”
Section: Post-traumatic Anxiety Is a Leading And Devastating Consequementioning
confidence: 99%